Ag‐Coupled Polymeric Nanohybrids with Synergistic Photodynamic and Photothermal Activities for Advanced Antibacterial Therapy. Issue 1 (23rd November 2021) - Liu, Bei; Liu, Yafang; Qin, Jinglei; Peng, Hongshang
Abstract: Considering the implications of inherent resistance of pathogenic bacteria, it is important to design a new generation of nonchemotherapic nanoagents for effective antibacterial therapy. Herein, we illustrate a one‐step reprecipitation‐encapsulation strategy to incorporate hydrophobic photosensitizers (ZnPc) and photothemal agents (dopamine hydrochloride) with a cationic poly‐L‐lysine (PLL) layer. Upon light irradiation, the polymeric nanohybrid exhibits high photo‐to‐thermal conversion efficiency (30.3%) and effective 1 O2 generation capability. To further enhance the antibacterial efficiency, Ag nanoparticle, a typical broad‐spectrum antibacterial agent, was decorated on the surface of PLL layer by in‐situ reduction. The as‐synthesized nanohybrids, referred to as ZnPc/DA@Ag, achieved a robust photodynamic/photothermal/Ag antibacterial capability without apparent systemic toxicity, thus holding great potential for broad‐spectrum eradication of pathogenic bacteria. Abstract : A nonchemotherapic antibacterial agent was synthesized through one‐step reprecipitation‐encapsulation of photosensitizers, photothemal agents and poly‐L‐lysine (PLL), followed by the in‐situ reduction of Ag on the surface of nanoparticle. The fabricated nanohybrids achieved a robust PDT/PTT/Ag antibacterial capability without apparent systemic toxicity.